Novel Single Phase Dc-Ac Inverter Topology With Enhanced Power Quality - Abdullah, Muhammad Faizal (2014)
Inverters are widely employed in many application such as photovoltaic (PV), uninterruptable power supply (UPS) etc for the conversion of direct current (DC) power to alternating current (AC) power. The key challenges in design and implementation of inverters are the realization of higher efficiency and good quality output power. To achieve these, this thesis presents a novel single phase DC-AC inverter topology with enhanced power quality. In this topology, a switch is connected at the lower arm of the full-bridge switches to control the output voltage across the full-bridge inverter. The switch at the lower arm of the full-bridge controls the output of full-bridge inverter by increasing or reducing the voltage level at the lower arm of the bridge. This switch of lower arm is controlled by a high frequency sinusoidal pulse width modulation (SPWM) switching signal. While the power switches of full-bridge inverter operate with square wave switching signal at a frequency of 50 Hz. The proposed topology produces a clean sinusoidal output waveform with low distortion and with minimum switching losses, thus yielding high quality output at high efficiency. Next, a random switching hybrid pulse width modulation (HPWM) inverter is developed in order to give a comparison between the proposed inverter and the random switching HPWM inverter. Both computer simulation and experiment were carried out to verify the performance of proposed topology. From the presented results, it is shown that proposed topology has superior performance compared to its conventional counterpart.